Adult education in the Nordic countries, Part 1 & 2 - Nordic Council of Ministers; European Centre for Leisure and Education (Czechoslovakia) (European Centre for Leisure and Education, 1989)
Contents.- Pt.1: Adult education in the Nordic countries. Denmark. Finland.- Pt.2: Iceland. Norway. Sweden Translated from "Voksenundervisningen i Norden" published by Nordisk Ministerråd, Copenhagen, 1982 Publication of the UNESCO-sponsored project "Organization and Structure of Adult Education in Europe"